Fiano, Greco and Falanghina grape cultivars differentiation by volatiles fingerprinting, a case study. Issue 8 (August 2019) - Carpentieri, Andrea; Sebastianelli, Angelo; Melchiorre, Chiara; Pinto, Gabriella; Trifuoggi, Marco; Lettera, Vincenzo; Amoresano, Angela
Abstract: The biomolecular characterization of edible products is gaining an increasing importance in food chemistry. The characteristic aroma or bouquet of a wine is the result of complex interactions of volatile molecules and odor receptors. Its characterization is the subject of many different studies, aimed at the development of new methods to be used for the discovery of frauds and for the typization of Protected Designation of Origin (P.D.O.) or Protected Geographic Indication (P.G.I.) wines. We previously outlined the proteomic profile of three cultivars of Vitis vinifera from South Italy (Campania) used for white wine production (Fiano, Greco and Falanghina) during the ripening. In this work, we present a mass spectrometry based study aimed at obtaining the profile of volatiles on the same samples using solid phase micro extraction coupled to gas chromatography. We demonstrated that some of the main constituents of aroma (namely terpenes, alcohols, aldehydes, etc.) were characteristic of certain grapes and absent in others.